ATTRACTING FOREIGN DIRECT INVESTMENT (FDI): STRATEGIES, EVIDENCE & VISUAL INSIGHTS - Alimov Bakhodir; Imomkulov Tulkin; Khatamov Nurbek (Modern American Journals, 2026)
Foreign Direct Investment (FDI) remains a cornerstone of economic development and global integration. As cross-border capital flows expand, countries compete to create attractive environments that encourage long-term investment. FDI supports infrastructure financing, technology transfer, employment growth, and export diversification — essential components for sustainable development.